Probing the stability of SrIrO3 during active water electrolysis via operando atomic force microscopy. Issue 2 (5th January 2023) - Akbashev, Andrew R.; Roddatis, Vladimir; Baeumer, Christoph; Liu, Tianchi; Mefford, J. Tyler; Chueh, William C.
Abstract : Using atomically flat SrIrO3 as a model electrocatalyst for water oxidation, we study the interplay between Sr 2+ leaching and perovskite dissolution at the nanometer scale through electrochemical atomic force microscopy. Abstract : Mechanistic studies of oxide electrocatalysts for heterogeneous water oxidation have been primarily focused on understanding the origins of activity, with fewer studies addressing fundamental properties that influence stability. The main challenge is directly observing and quantifying local structural instability under operating conditions. In this work, we provide a dynamic view of the perovskite stability as a function of time and operational voltage using operando electrochemical atomic force microscopy (EC-AFM). Specifically, we study the degradation pathways of SrIrO3, a highly active electrocatalyst, during the oxygen evolution reaction (OER) by tracking the potential-dependent Sr leaching and perovskite dissolution at the nanometer scale. This material serves as a model system for degradation studies of perovskite AMO3 oxides, exhibiting both A-cation leaching and transition metal (M) dissolution. We show that Sr leaching precedes perovskite dissolution by up to 0.8 V, leading to a wide voltage window of stability where water oxidation occurs on a Sr-depleted surface without significant corrosion. Moreover, we reveal that the stability of the perovskite surface is strongly influenced by the electrolytic environment and that corrosion rates differ dramatically as a function of dissolved Sr concentration. Ultimately, our study demonstrates that the overall stability of perovskite oxides during electrocatalysis can be substantially improved by suppressing A-site leaching.